Jacob's Disease: case report - Marilia de Oliveira Coelho Dutra LEAL; Leonard Duarte MOREIRA; Fabrício PASSADOR-SANTOS; Andressa Borges SOARES; Rubens Gonçalves TEIXEIRA; Cláudio Roberto Pacheco JODAS (Faculdade São Leopoldo Mandic, 2021)
ABSTRACT Jacob's disease or osteochondroma is a rare disease that presents as a pseudo-joint between the coronoid process of the mandible and the posterior surface of the zygomatic bone. The present case report is of an 11-year-old female patient with a maximum mouth opening of 2mm. When evaluating computed tomography with three-dimensional reconstruction, a mushroom-shaped increase in the coronoid process of the mandible on the left side was observed, intimately connected to the zygomatic bone (inferoposterior region of the body of the zygoma), which suggests a pseudoarticulation. Surgical removal of the tumor mass was performed under general anesthesia via intraoral access and is called coronoidectomy. Histopathological, the presence of hyaline cartilage was observed, a condition that is pathognomonic for Jacob's Disease. Jacob's disease case reports are still rare in the literature, with mushroom shape and histopathological confirmation due to the presence of hyaline cartilage.